2020
DOI: 10.1177/0300060520934297
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal long non-coding RNA H19 as a potential novel diagnostic and prognostic biomarker for gastric cancer

Abstract: Objective Long non-coding RNAs (lncRNAs) are involved in carcinogenesis and could be used as diagnostic biomarkers. Our study aimed to elucidate the clinical role of serum exosomal lncRNA H19 in gastric cancer (GC). Methods In this prospective clinical study, we determined serum exosomal lncRNA H19 levels in 81 patients with GC and analysed the correlations between serum lncRNA H19 levels and clinical characteristics. Receiver operating characteristics (ROC) curves were constructed to determine the diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In recent years, great progress has been made in the research on the relationship between lncRNAs and tumor development and metastasis [11,12]. H19 was negatively correlated with the prognosis of GC and played the carcinogenic role by regulating miRNAs and genes in GC [13][14][15]. PINT was found to suppress tumor progression by the crosstalk with miR-21 in GC [16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great progress has been made in the research on the relationship between lncRNAs and tumor development and metastasis [11,12]. H19 was negatively correlated with the prognosis of GC and played the carcinogenic role by regulating miRNAs and genes in GC [13][14][15]. PINT was found to suppress tumor progression by the crosstalk with miR-21 in GC [16].…”
Section: Introductionmentioning
confidence: 99%
“…Their AUCs were 0.849 and 0.776, respectively, which were higher than the diagnostic efficiencies of traditional diagnostic markers (CEA, CA19-9, and CA72-4). Furthermore, their expression levels were significantly correlated with the TNM stage (173,174).…”
Section: Diagnostic and Prognostic Markersmentioning
confidence: 93%
“…Their AUCs were 0.849 and 0.776, respectively, which were higher than the diagnostic efficiencies of traditional diagnostic markers (CEA, CA19-9, and CA72-4). Furthermore, their expression levels were significantly correlated with the TNM stage ( 173 , 174 ). Lnc-SLC2A12-10:1 was also evidently related to GC tumor size, lymph node metastasis, and degree of differentiation ( 174 ).…”
Section: Potential Clinical Application Of Exosomal Ncrnas In Gcmentioning
confidence: 96%
“… 261 Serum samples from 81 patients with gastric cancer showed that exosomes contained significant levels of long non-coding RNA (lncRNA) H19, which could be a diagnostic marker for gastric cancer. 262 Plasma exosomes are suitable candidates as biomarkers for various diseases. For instance, plasma exosome lncRNA expression profiles were examined in esophageal squamous cell carcinoma (ESCC) patients.…”
Section: Exosomes As Diagnostic Markersmentioning
confidence: 99%